Paediatric medicine issues and gaps from healthcare workers point of view: survey results and a narrative review from the global accelerator for paediatric formulations project - Barbieri, Elisa; Minotti, Chiara; Cavagnis, Sara; Giaquinto, Carlo; Cappello, Bernadette; Penazzato, Martina; Lallemant, Marc (Frontiers in Pharmacology, 2023)
The WHO Model List of Essential Medicines for Children (EMLc) has not been systematically revised in the last few years. We conducted a survey addressed to healthcare professionals prescribing, preparing, or administering medicines to children and a narrative review to identify problematic paediatric formulations or missing medicines in all therapeutic fields to inform the review of the EMLc in 2023. A total of 285 physicians (67%), 28 nurses (6%) and 142 pharmacists (31%), mostly working in the hospital setting, reported at least one problematic medicine. 290 medicines were reported as missing (completely or the child-appropriate formulation). The top three most mentioned were ciprofloxacin together with phenobarbital and omeprazole. 387 medicines were reported as problematic (34% were oral liquid formulations, 34% tablets, 18% parenteral preparations. Most of the products were antibacterials (27%), cardiovascular medicines (11%) and antivirals (11%). The obtained responses show the perspective of healthcare workers working around the world, particularly in the European region, in the African region, and in the Region of the Americas, with limited representation from Northern Africa and the Middle East. Our results need to be analysed with the outputs of other ongoing works before specific products can enter the GAP-f prioritisation process. Efforts to develop oral liquid formulations for children should be accelerated so that the uncertainties associated with off-label drug preparation and use are minimised, and therapeutic benefits are optimised.